Tantangan Implementasi Corporate Social Responsibility Perusahaan Saat Pandemi Covid-19 Tahun 2020-2022 - Resty Amanda Erbhasan; Lucy Pujasari Supratman (Universitas Prof. Dr. Moestopo (Beragama), 2023)
During the current Covid-19 pandemic, many sectors were paralyzed and affected and affected the people's economy during the pandemic. CSR as a form of company activity has become a breath of fresh air for the community during the increasing number of the Covid-19 pandemic that has entered Indonesia. The discussion of this research aims to determine the obstacles to corporate social responsibility (CSR) faced by PT Vale Indonesia Tbk while implementing the CSR program to strengthen local communities in dealing with the COVID-19 outbreak. The population taken from this research is PT Vale Indonesia's CSR report during the pandemic, while the sample is PT Vale Indonesia's CSR report for 2020-2022. This type of research uses a qualitative approach with the case study method. The results of the study show that there are three challenges that hinder the CSR program and three implementations found in the company's CSR program. Due to the Covid-19 pandemic, several of these aspects have hindered the sustainability of PT Vale Indonesia's CSR program, namely Community Development and Empowerment (PPM). Where this program wants to involve the community gathering in large numbers for a local event, as well as the existence of licensing barriers from the local government. Overall, the community has greatly benefited from the PPM program during the pandemic and this program has received broad support from the communities within the area.